Some aspects of the acute phase immune response to a lipopolysaccharide (LPS) challenge are mitigated by supplementation with a Saccharomyces cerevisiae fermentation product in weaned beef calves,. Issue 3 (24th August 2020) - Burdick Sanchez, Nicole C; Carroll, Jeff A; Broadway, P Rand; Edrington, Tom S; Yoon, Ilkyu; Belknap, Craig R
Abstract: This study was conducted to determine if feeding a Saccharomyces cerevisiae fermentation product (SCFP) to calves would alter the acute phase response to a lipopolysaccharide (LPS) challenge. Crossbred steer calves [ n = 32; 274 ± 1.9 kg body weight (BW)] were randomly allotted to two treatment diets for 21 d: 1) control, fed RAMP (Cargill, Dalhart, TX) and 2) SCFP, fed the control ration supplemented with NaturSafe at 12 g/hd/d mixed into the TMR (NaturSafe, Diamond V, Cedar Rapids, IA). On day 22, steers were fitted with indwelling jugular catheters and rectal temperature monitoring devices and placed in individual bleeding stalls. On day 23, steers were challenged i.v. with 0.25 µg/kg BW LPS. Blood samples were collected at 0.5-h (serum) or 2-h (complete blood counts) intervals from −2 to 8 h and again at 24 h relative to the LPS challenge at 0 h. Sickness behavior scores (SBS) were recorded after the collection of each blood sample. Rectal temperatures were greater in SCFP steers from 6 to 11 h, at 13 h, from 15 to 20 h, and from 22 to 24 h following the LPS challenge compared to Control steers (treatment × time: P = 0.01). Additionally, SCFP-supplemented steers had reduced ( P < 0.01) SBS compared to Control steers. Platelet concentrations remained greater in SCFP-supplemented steers compared to Control steers throughout the study ( P = 0.05), while there was a tendency ( P = 0.09) for SCFP steers to have greater white blood cells and eosinophils concentrations than Control steers. There was a treatment × time interaction for serum cortisol and glucose ( P < 0.01). Specifically, cortisol was greater at 0.5 and 2 h postchallenge but was reduced at 3 h for SCFP steers compared to Control steers. Glucose was greater in SCFP steers at −0.5, 2, and 7.5 h compared to Control steers. Serum amyloid A was reduced in SCFP steers at 0.5 h, yet greater at 1 and 7.5 h postchallenge compared to Control steers (treatment × time: P < 0.01). Fibrinogen concentrations were greater ( P < 0.01) in SCFP compared to Control steers. There was a treatment × time interaction ( P < 0.01) for tumor necrosis factor-α (TNF-α) such that concentrations were reduced in SCFP steers from 1 to 2 h postchallenge compared to Control steers. Overall, these data suggest that supplementing calves with SCFP may have primed the innate immune response prior to the challenge, particularly platelets, which resulted in an attenuated sickness behavior and TNF-α response to LPS.